Can clinicians and scientists explain and prevent unexplained underperformance syndrome in elite athletes: an interdisciplinary perspective and 2016 update. Issue 1 (25th November 2015) - Lewis, Nathan A; Collins, Dave; Pedlar, Charles R; Rogers, John P
Abstract : The coach and interdisciplinary sports science and medicine team strive to continually progress the athlete's performance year on year. In structuring training programmes, coaches and scientists plan distinct periods of progressive overload coupled with recovery for anticipated performances to be delivered on fixed dates of competition in the calendar year. Peaking at major championships is a challenge, and training capacity highly individualised, with fine margins between the training dose necessary for adaptation and that which elicits maladaptation at the elite level. As such, optimising adaptation is key to effective preparation. Notably, however, many factors (eg, health, nutrition, sleep, training experience, psychosocial factors) play an essential part in moderating the processes of adaptation to exercise and environmental stressors, for example, heat, altitude; processes which can often fail or be limited. In the UK, the term unexplained underperformance syndrome (UUPS) has been adopted, in contrast to the more commonly referenced term overtraining syndrome, to describe a significant episode of underperformance with persistent fatigue, that is, maladaptation. This construct, UUPS, reflects the complexity of the syndrome, the multifactorial aetiology, and that 'overtraining' or an imbalance between training load and recovery may not be the primary cause for underperformance. UUPS draws on the distinction that a decline in performance represents the universal feature. In our review, we provide a practitioner-focused perspective, proposing that causative factors can be identified and UUPS explained, through an interdisciplinary approach (ie, medicine, nutrition, physiology, psychology) to sports science and medicine delivery, monitoring, and data interpretation and analysis.